2014
DOI: 10.1097/gco.0000000000000077
|View full text |Cite
|
Sign up to set email alerts
|

The techniques and outcomes of hysteroscopic metroplasty

Abstract: The hysteroscopic metroplasty with its simplicity, safety, and improved reproductive outcomes has liberalized the approach to treatment. Today, hysteroscopic metroplasty is a common practice to treat septate uterus with salutary effects both in infertile patients and in patients with recurrent pregnancy loss or premature labor, especially if in-vitro fertilization is being contemplated. Decisions on when to treat uterine septa are discussed in particular because of lack of prospective, randomized controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 55 publications
(50 reference statements)
0
14
0
1
Order By: Relevance
“…Hysteroscopic metroplasty seems to significantly improve the obstetric outcome in a population of women with previous miscarriage. The procedure seems to be safe when done by skilled surgeons [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hysteroscopic metroplasty seems to significantly improve the obstetric outcome in a population of women with previous miscarriage. The procedure seems to be safe when done by skilled surgeons [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women with a history of miscarriages ( Valle and Ekpo, 2013 ) and infertility ( Pabuçcu and Gomel, 2004 ; Mollo et al , 2009 ), after diagnosis of septate uterus by ASRM classification criteria, commonly undergo hysteroscopic metroplasty to improve reproductive outcomes ( Grimbizis et al , 2001 ; Brucker et al , 2011 ; Paradisi et al , 2014 ). Many non-controlled studies have confirmed the validity of such a procedure ( Nouri et al , 2010 ; Valle and Ekpo, 2013 ), although we are waiting for confirmation in randomized controlled trials ( Christiansen et al , 2005 ; Bosteels et al , 2010 ; Kowalik et al , 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in RIF cases without endometrial pathology monopolar electrocoagulation to 1-3 regions was implemented as a standard approach in the study group. Supporting our method, a recent review evaluating hysteroscopic septum resection in infertile patients, suggested electro-surgery with specially designed electrodes fitting to the hysteroscope as a safe method for reproductive functions [27]. Hysteroscopy has been reported to be a positive prognostic factor for women with RIF in order to conceive in the subsequent IVF cycle [5,28].…”
Section: Discussionmentioning
confidence: 90%